WormPaths: Caenorhabditis elegans metabolic pathway annotation and visualization. Issue 1 (12th June 2021) - Walker, Melissa D; Giese, Gabrielle E; Holdorf, Amy D; Bhattacharya, Sushila; Diot, Cédric; García-González, Aurian P; Horowitz, Brent B; Lee, Yong-Uk; Leland, Thomas; Li, Xuhang; Mirza, Zeynep; Na, Huimin; et al.
Abstract: In our group, we aim to understand metabolism in the nematode Caenorhabditis elegans and its relationships with gene expression, physiology, and the response to therapeutic drugs. Visualization of the metabolic pathways that comprise the metabolic network is extremely useful for interpreting a wide variety of experiments. Detailed annotated metabolic pathway maps for C. elegans are mostly limited to pan-organismal maps, many with incomplete or inaccurate pathway and enzyme annotations. Here, we present WormPaths, which is composed of two parts: (1) the careful manual annotation of metabolic genes into pathways, categories, and levels, and (2) 62 pathway maps that include metabolites, metabolite structures, genes, reactions, and pathway connections between maps. These maps are available on the WormFlux website. We show that WormPaths provides easy-to-navigate maps and that the different levels in WormPaths can be used for metabolic pathway enrichment analysis of transcriptomic data. In the future, we envision further developing these maps to be more interactive, analogous to road maps that are available on mobile devices.